PERAN MEMETIC IKLAN DALAM PEMBENTUKAN BUDAYA BELANJA KONSUMEN DI KOTA PALU, SULAWESI TENGAH - Yulianti Bakari; Ikhtiar Hatta; Citra Dewi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
This study presents an understanding of the role of advertising in shaping the world of shopping; therefore, the world of shopping does not only contain the transaction process in the buying and selling process. This study operationalizes the mimetic approach to analyzing the shopping phenomenon and advertising determinants. This study uses a research method that is generally carried out in anthropology, namely observation and interviews with consumers (especially teenagers) in Palu City. Besides that, it also develops deepening through the literature review. As a result, shopping today has become a lifestyle formed by the determination of advertising meaning that the advertising and shopping culture phenomena in this study are articulated as a phenomenon that intertwines to form a cultural system with its logic as a social phenomenon. As in Kaili's land, shopping expression certainly has its uniqueness amid the influence of globalization which encourages every consumer to follow a single image disseminated by advertisements.